Therapeutic efficacy of artemether-lumefantrine against uncomplicated Plasmodium falciparum malaria in a high-transmission area in northwest Ethiopia - Teklemariam, Michael; Assefa, Ashenafi; Kassa, Moges; Mohammed, Hussien; Mamo, Hassen (PLOS ONE, 2017)
Malaria, particularly due to Plasmodium falciparum, remains a major public health threat in Ethiopia. Artemether-lumefantine (AL) has been the first-line antimalarial drug against uncomplicated P. falciparum malaria in the country since 2004. Regular monitoring of antimalarial drugs is recommended by the World Health Organization (WHO) to help early detection of drug resistant strains of the parasite and contain their rapid spread. The objective of this study was to assess the therapeutic efficacy of AL in a high-transmission setting in Ethiopia. The study site was Setit Humera, northwest Ethiopia. Single-arm prospective study of a 28-day follow-up was conducted from October 2014 to January 2015 according to the revised WHO 2009 drug efficacy study protocol. Study end-points were classified into primary end-point and secondary end-point. While the primary end-point was the day-28 adequate clinical and parasitological response the secondary end-points were clinical and parasitological evaluations (parasite, fever and gametocyte clearance rate, incidence of drug adverse events) and the relative increment in hemoglobin (Hb) level from baseline to day (D) 14 and D28. A total of 92 patients were enrolled and 79 had completed the 28-day follow-up period. The overall cure rate was 98.8% with 95% confidence interval of 0.915–0.998 without polymerase chain reaction correction. The parasite clearance rate was high with fast resolution of clinical symptoms; 100% of the study participants cleared parasitaemia and fever on D3. Gametocyte carriage was reduced from 7% on D0 to 1% on D3 and complete clearance was achieved on D14. Mean Hb concentration significantly increased on D28 compared to that on D14. There was no serious adverse event. AL was efficacious and safe in a high-transmission setting for treatment of uncomplicated falciparum malaria.